A segurança jurídica dos smart contracts nas transações executadas na tecnologia blockchain - Munaretto, Taís (My University, 2019)
Smart contracts are created by computer codes, which aim for automatic execution of terms pre-established in the contract by the parties, through situations that can be verified. They are the result of technological advances and modern society. In the meantime, this research aims to verify the legal certainty brought by smart contracts, through transactions executed in blockchain technology. For this, we analyzed the main contractual principles and the essential elements that govern the traditional contracts in our legal sphere, dealing more specifically with the agent, object and form of the contracts, to verify the validity and effectiveness of the contractual relations produced by this new instrument. In addition, the legal nature of cryptocurrencies and their framing in relation to smart contracts, when used as a form of payment, considered as commodities, were analyzed. In this case, the contracts are treated as barter. In other forms, the typicality of the contracts according to the agreed covenants, just as the traditional contracts should be observe. In this assertion, the main objective of the present work was to understand how smart contracts are viewed by brazilian law and to show which directions the legislative power may take when dealing with this subject. It was found, through bibliographic research and deductive hypothetical method, partially inductive, that smart contracts are the automation of processes and therefore follow the principles that rules the formation of contracts, observing their essential elements. From this perspective, they are also considered valid and effective. However, despite the legal certainty brought by its form, there are still numerous problems facing the application and interpretation of this new technology, especially in the procedural sphere, as regards the contractual review or the resolution of smart contracts through court decisions. These characteristics are considered unchanged, which highlights the importance of the theme for legal science (sic).
Smart contracts são criados por meio de códigos computacionais, que visam à execução automática dos termos preestabelecidos no contrato pelas partes, mediante situações que possam ser verificadas. Nesse ínterim, esta pesquisa buscou verificar a segurança jurídica trazida pelos smart contracts, através das transações executadas na tecnologia blockchain. Para isso, foram analisados os principais princípios contratuais e os elementos essenciais que regem os contratos tradicionais em nossa esfera jurídica, tratando-se mais especificamente do agente, objeto e forma dos contratos, a fim de averiguar a validade e a eficácia das relações contratuais produzidas por este novo instrumento. Ademais, foram analisados a natureza jurídica das criptomoedas e seu enquadramento diante dos smart contracts, quando utilizadas como forma de pagamento, consideradas como commodities. Nesse caso, os contratos são tratados como permutas. Nas demais formas, devem observar a tipicidade dos contratos de acordo com as avenças estipuladas, do mesmo modo que os contratos tradicionais. Nessa assertiva, o principal objetivo do presente trabalho foi entender como os smart contracts são vistos frente à legislação brasileira e apontar quais rumos que o poder legislativo poderá tomar ao tratar sobre esse assunto. Constatou-se, por meio de pesquisa bibliográfica e método hipotético dedutivo, parcialmente indutivo, que os smart contracts são a automatização dos processos e seguem, portanto, os princípios que regem à formação dos contratos, observando seus elementos essenciais. Nessa perspectiva, são também considerados válidos e eficazes. Todavia, apesar da segurança jurídica trazida pela sua forma, ainda são inúmeros os problemas enfrentados diante da aplicação e interpretação dessa nova tecnologia, principalmente na esfera processual, no que tange à revisão contratual ou à resolução dos contratos inteligentes mediante decisões judiciais. Essas características são consideradas, assim, inalteráveis, o que evidencia a importância do tema para a ciência jurídica (sic).
Keywords: Contratos; Garantia (Direito)